Glycine-modulated Zirconium Perylene-based Metal-Organic Framework for Rhodamin B Photocatalytic Degradation - Zulys, Agustino; Defania, Mella; Gunlazuardi, Jarnuzi; Adawiah, Adawiah (Universitas Jenderal Soedirman, 2023)
Photocatalysis employing Metal-Organic Framework (MOF) material may degrade Rhodamin B pollutant. MOF photocatalytic activity can be adjusted by altering the ligands, metal ions, and modulators. This research aims to synthesize glycine-modulated zirconium perylene-based metal organic framework (Zr-PTCA-Gly) for Rhodamin B photocatalytic degradation under visible light irradiation. The activated Zr-PTCA-Gly exhibits good catalytic activity to degrade Rhodamine B with a 95% degradation efficiency.